Domestic GHG emissions and the responsibility of households in Spain: looking for regional differences. Issue 53 (14th November 2017) - Duarte, Rosa; Mainar-Causapé, Alfredo J.; Sánchez Chóliz, Julio
ABSTRACT: The aim of this article is to analyze the responsibilities of Spanish households, as final consumers, for the generation of domestic greenhouse gases emissions (GHG), by region of residence, distinguishing between NUTS 1 and NUTS 2 (autonomous regions). The motivation is the process of convergence experimented by Spanish regions based on the strong economic growth experienced by the country until 2008, which could results in different emissions responsibilities because of different lifestyles and production structures. We examine in depth the relationships between a representative household in each region and its patterns of consumption. Although we do find a relationship between per capita income and regional responsibility for pollution generation, it is based on a demand scale effect, which overlaps the effects of the regional consumption patterns. Thus, in the richest regions (Madrid, Northeast, East), despite their having a less polluting pattern than other regions, the level of per capita embodied emissions is higher, due to their higher level of consumption. This scale effect, and the linkages between regional responsibilities for emissions and household consumption patterns are analyzed using linear models based on Social Accounting Matrices. The basis of the estimations is the regional emission intensity (average emission per euro spent by each type of regional home).